Outcomes of patients with hepaticojejunostomy anastomotic strictures undergoing endoscopic and percutaneous treatment - Choi, Kevin Kyung Ho; Bonnichsen, Mark; Liu, Ken; Massey, Saniya; Staudenmann, Dominic; Saxena, Payal; Kaffes, Arthur John (Endoscopy International Open, 2023)
Background and study aims The increase in hepaticojejunostomies has led to an increase in benign strictures of the anastomosis. Double balloon enteroscopy-assisted ERCP (DBE-ERCP) and percutaneous transhepatic biliary drainage (PTBD) are treatment options; however, there is lack of long-term outcomes, with no consensus on management. We performed a retrospective study assessing the outcomes of patients referred for endoscopic management of hepaticojejunostomy anastomotic strictures (HJAS).Patients and methods All consecutive patients at a tertiary institution underwent endoscopic intervention for suspected HJAS between 2009 and 2021 were enrolled.Results Eighty-two subjects underwent DBE-ERCP for suspected HJAS. The technical success rate was 77 % (63/82). HJAS was confirmed in 41 patients. The clinical success rate for DBE-ERCP ± PTBD was 71 % (29/41). DBE-ERCP alone achieved clinical success in 49 % of patients (20/41). PTBD was required in 49 % (20/41). Dual therapy was required in 22 % (9/41). Those with liver transplant had less technical success compared to other surgeries (72.1 % vs 82.1 % P = 0.29), less clinical success with DBE-ERCP alone (40 % vs 62.5 % P = 0.16) and required more PTBD (56 % vs 37.5 % P = 0.25). All those with ischemic biliopathy (n = 9) required PTBD for clinical success, required more DBE-ERCP (4.4 vs 2.0, P = 0.004), more PTBD (4.7 vs 0.3, P < 0.0001), longer treatment duration (181.6 vs 99.5 days P = 0.12), and had higher rates of recurrence (55.6 % vs 30.3 % P = 0.18) compared to those with HJAS alone. Liver transplant was the leading cause of ischemic biliopathy (89 %). The overall adverse event rate was 7 %.Conclusions DBE-ERCP is an effective diagnostic and therapeutic tool in those with altered gastrointestinal anatomy and is associated with low complication rates.